2018
DOI: 10.1002/star.201700322
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in Structural, Physicochemical, and Digestive Properties of Red Adzuki Bean Starch after Repeated and Continuous Annealing Treatments

Abstract: Red adzuki bean starch-water suspensions (1:3, w/v) are subjected to repeated and continuous annealing treatments at 55 C for 96 h. The changes in structural, physicochemical, and digestive properties of starch after both treatments are studied and compared. The results show that the repeated and continuous annealing increases the relative crystallinity of starch without influencing the morphological structure and crystalline patterns. Gelatinization temperatures and enthalpy increase; however starch solubilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 33 publications
13
43
0
Order By: Relevance
“…Compared with the native starch, the RDS level of the annealed samples became lower with the increase of annealing cycles and time, but the RS, SDS (except the samples of CANN‐96), and the RS + SDS level gradually increased (Table ). These results were in agreement with that of the red adzuki bean starch (Xu et al., ). However, the RS content of the annealed navy and pea bean starch decreased after annealing treatment (Chung et al., ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Compared with the native starch, the RDS level of the annealed samples became lower with the increase of annealing cycles and time, but the RS, SDS (except the samples of CANN‐96), and the RS + SDS level gradually increased (Table ). These results were in agreement with that of the red adzuki bean starch (Xu et al., ). However, the RS content of the annealed navy and pea bean starch decreased after annealing treatment (Chung et al., ).…”
Section: Resultssupporting
confidence: 92%
“…From the findings, it was suggested that the solubility and swelling power of sweet potato starch gradually decreased with the increase of the number of cycles or time of annealing (Table ). These results were in agreement with the solubility and swelling power of red adzuki bean starch (Xu et al., ). This could be attributed to the formation of the amylose–lipid complexes and a more ordered structure of the amorphous regions (Chung, Liu, & Hoover, ; Waduge et al., ).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations